2017
DOI: 10.1024/0301-1526/a000621
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative injury associated with stenting of asymptomatic carotid artery stenosis

Abstract: Summary:Background: After carotid artery stenting (CAS), neurological complications that cannot be explained with imaging methods may develop. In our study we aimed to show, using oxidative stress markers, isolated oxidative damage and resulting neurological fi ndings following CAS in patients with asymptomatic carotid artery stenosis. Patients and methods: We included 131 neurologically asymptomatic patients requiring CAS. The neurological fi ndings were evaluated using the modifi ed Rankin Scale (mRS) prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Vasodilation and contraction are maintained by vascular endothelial cells, whose damage is the pathological basis of atherosclerosis. Contractile and diastolic factors synthesized and secreted by vascular endothelial cells can maintain vasoconstrictive functions [1,2]. As an early symptom of atherosclerosis, endothelial cell injury induces the generation of pathological stress and impairs normal vasomotor functions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Vasodilation and contraction are maintained by vascular endothelial cells, whose damage is the pathological basis of atherosclerosis. Contractile and diastolic factors synthesized and secreted by vascular endothelial cells can maintain vasoconstrictive functions [1,2]. As an early symptom of atherosclerosis, endothelial cell injury induces the generation of pathological stress and impairs normal vasomotor functions [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Vasa -European Journal of Vascular Medicine Saraçoğlu et al [3] have shown the possible correlation between oxidative damage and neurological fi ndings after CAS, which could not be explained in the diff usion-weighted magnetic resonance imaging (DW-MRI). Interestingly, the authors have analysed the oxidative stress and correlated these results with the results of DW-MRI, evidencing that an impaired level of cerebral blood fl ow autoregulation, leading frequently to cerebral hyperperfusion syndrome after CAS, can better be detected with biomarkers of oxidative stress than with MRI.…”
mentioning
confidence: 99%